Uji Potensi Antituberkulosis Ekstrak N-Heksan dan Ekstrak Etanol Daun Jeruk Nipis (Citrus Aurantiifolia) secara in Vitro - Putri, Alya Rosandiyus; Fatimah, Cut; Gunawan, Muhammad; Safriana, Safriana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Tuberculosis is a disease caused by Mycobacterium tuberculosis which is widely suffered and causes death. Currently, antituberculosis treatment using synthetic chemicals has been widely resistant. The purpose of this study was to test the potential of lime extract to inhibit the growth of tuberculosis bacteria. This research method uses a quantitative approach and is experimental. The results of the study showed that the results of the phytochemical screening test showed the same group of chemical compounds in fresh leaves, simplex and ethanol extract of lime leaves, namely alkaloids, flavonoids, tannins, saponins, steroids and glycosides. While the n-hexane extract only contains steroids and glycosides. Then the effectiveness of antituberculosis can be seen from the ethanol extract being stronger than the n-hexane extract, namely in the 1st week there was inhibition while the n-hexane extract from the 1st week to the 4th week had bacterial growth.